2017
DOI: 10.1002/ehf2.12180
|View full text |Cite
|
Sign up to set email alerts
|

Lower than expected burden of premature ventricular contractions impairs myocardial function

Abstract: AimsWe aimed to explore the burden of frequent premature ventricular contractions (PVCs) associated with myocardial dysfunction in patients with outflow tract arrhythmia (OTA). We hypothesized that this threshold is lower than the previously suggested threshold of 24 000 PVCs/24 h (24%PVC) when systolic function is assessed by strain echocardiography. Furthermore, we aimed to characterize OTA patients with malignant arrhythmic events.Methods and resultsWe included 52 patients referred for OTA ablation (46 ± 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…A daily PVC burden between 16% and 24% of all heartbeats have been associated to progressive LV dysfunction . However, subtle myocardial mechanical dysfunction detected by speckle tracking echocardiography has been reported also in patients with a PVC burden as low as 4% . Left bundle‐branch block (LBBB) PVC‐QRS morphology and longer PVC‐QRS duration (>150 ms) as well as an epicardial origin of PVCs require a lower arrhythmic burden to develop LV dysfunction, thus corroborating the hypothesis of mechanical dyssynchrony as the main mechanism of PVC‐induced cardiomyopathy .…”
Section: Pvc‐induced Cardiomyopathymentioning
confidence: 77%
See 1 more Smart Citation
“…A daily PVC burden between 16% and 24% of all heartbeats have been associated to progressive LV dysfunction . However, subtle myocardial mechanical dysfunction detected by speckle tracking echocardiography has been reported also in patients with a PVC burden as low as 4% . Left bundle‐branch block (LBBB) PVC‐QRS morphology and longer PVC‐QRS duration (>150 ms) as well as an epicardial origin of PVCs require a lower arrhythmic burden to develop LV dysfunction, thus corroborating the hypothesis of mechanical dyssynchrony as the main mechanism of PVC‐induced cardiomyopathy .…”
Section: Pvc‐induced Cardiomyopathymentioning
confidence: 77%
“…16 However, subtle myocardial mechanical dysfunction detected by speckle tracking echocardiography has been reported also in patients with a PVC burden as low as 4%. 17 (AADs) or CA. 19 In this regard, several factors have been linked with reversible cardiomyopathy after successful treatment of PVCs including a pre-treatment PVC burden of at least 10% and absence of myocardial scar detectable by late gadolinium enhancement (LGE) CMR.…”
Section: Pvc-induced Cardiomyopathymentioning
confidence: 99%
“…166,168 A recent study measuring subtle degrees of LV impairment by using speckle tracking echocardiography (measuring LV global longitudinal strain and mechanical dispersion) showed mild impairment of myocardial function with a PVC burden >8%. 169 The wide range reported in studies may be partly explained by the singleday Holter monitoring used. A wide daily variation in PVC burden is well recognized.…”
Section: Consensus Statements Symbol Referencesmentioning
confidence: 99%
“…14 In several studies in the literature, it was reported that LV-GLS value obtained with STE significantly decreased in patients with normal LVEF with frequent PVCs. 16,17,[23][24][25] In addition to LV-GLS, the LA-GLS was also evaluated, and it was reported that both LA-GLS and LV-GLS values decreased in PVCs patients with normal LVEF. 24 Although LVEF reduction in PVCs patients is more common in patients with PVCs burden ≥20%, less frequent PVCs burden >8% are reported to be sufficient to reduce LV-GLS.…”
Section: Discussionmentioning
confidence: 99%
“…19,21,22 In a limited number of recent studies, LV-GLS evaluation has been performed in patients with PVCs and preserved LVEF. 16,[23][24][25] In these studies, there is evidence that LV-GLS decreases in patients with PVCs and preserved LVEF. 16,[23][24][25] As far as we have investigated, there is no clear information about the evaluation of LA-GLS in patients with PVCs and reduced LVEF and the effect of RFA treatment on LV-GLS in these patients.…”
Section: Introductionmentioning
confidence: 95%